2020
DOI: 10.1186/s12864-020-06826-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and comparison of differentially expressed profiles of miRNAs and lncRNAs with associated ceRNA networks in the gonads of Chinese soft-shelled turtle, Pelodiscus sinensis

Abstract: Background: The gonad is the major factor affecting animal reproduction. The regulatory mechanism of the expression of protein-coding genes involved in reproduction still remains to be elucidated. Increasing evidence has shown that ncRNAs play key regulatory roles in gene expression in many life processes. The roles of microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in reproduction have been investigated in some species. However, the regulatory patterns of miRNA and lncRNA in the sex biased expression of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…It has also been reported that MALAT1 plays an important role in DM and its complications. 54 , 55 Li et al 35 found the expression of MALAT1 increased and that of miR-23c decreased in rats with streptozotocin-induced DM and HG-induced HK-2 renal tubular epithelial cells. Downregulation of MALAT1 expression or upregulating miR-23c expression might inhibit pyroptosis, with decreased expression of NLRP3, caspase-1 and IL-1β, suggesting that downregulation of MALAT1 inhibits pyroptosis induced by HG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that MALAT1 plays an important role in DM and its complications. 54 , 55 Li et al 35 found the expression of MALAT1 increased and that of miR-23c decreased in rats with streptozotocin-induced DM and HG-induced HK-2 renal tubular epithelial cells. Downregulation of MALAT1 expression or upregulating miR-23c expression might inhibit pyroptosis, with decreased expression of NLRP3, caspase-1 and IL-1β, suggesting that downregulation of MALAT1 inhibits pyroptosis induced by HG.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are noncoding RNAs that regulate gene expression, for example by inhibiting lncRNAs near target genes in the cell nucleus. 55 The mechanisms of miRNA regulation of target genes need further investigation. MiR-200c, a member of miR-200 family, is involved in the regulation of OS.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous research, Ma et al and Liu et al found that miRNAs and lncRNA were involved in gonadal development [47,48]. The discovery of small RNAs such as miRNAs, snRNAs, and other types had unveiled a slew of powerful regulators of gene expression in recent years [49].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found 665 differentially expressed miRNAs, with 519 being up-regulated in testis and 146 being down-regulated in ovary, respectively [48]. A total of 633 miRNAs showed differential expression in the ovaries and testes [47]. However, the molecular mechanism of miRNA regulating gonadal differentiation is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear miRNAs may recognize and bind target sequences in gene promoters and other DNA regulatory elements in a sequence-specific manner, and then recruit proteins or complexes responsible for epigenetic modification, which results in chromatin remodeling, resulting in transcriptional activation or gene silencing. Alternatively, nuclear miRNAs inhibit lncRNAs near target genes, thereby regulating gene expression (40). At present, the reasons, mechanisms, and functions of miRNA accumulation in the nucleus remain unclear and require further investigation.…”
Section: Mirna Functionmentioning
confidence: 99%